Unveiling the thermodynamic and kinetic mechanisms of acaiomass pyrolysis for Fe-N Co-doped biochar - Shouzhi Li; Haolin He; Haoyu Yao; Linghui Yu; Yuankuo Lv; Yinping Zhao; Xiangguang Meng; Wei Chen (Biomass and Bioenergy, 2027)

HSF4 alleviates ferroptosis in colorectal cancer through transcriptional regulation of MBOAT1/2 - Kelin Yue; Haolin Wu; Kexin Li; Shu Yang; Xuan Bai; Wenjing Zhang; Yu Zhang (Functional & Integrative Genomics, 2026)

Unlocking the black box: Soil C:N:P stoichiometry mediates microbial controls on nitrogen and phosphorus runoff losses in agroecosystems - Yi Wang; Junjia Qi; Meihui Wang; Zhenke Zhu; Yong Li; Zhenghui Lv; Jinyi Yu; Haolin Yang; Jian Liu; Yuchen Lv; Ying Zhao (Agriculture, Ecosystems & Environment, 2026)

Biological recovery of waste lithium-ion battery cathode materials: Recent advancements - Haolin Li; Senshen Yu; Shuaizhe Li; Mengke Dong; Yunke Wang; Huijun Fan; Yadong Wang; Xingyong Li; Na Liu; Xuexiang Fu; Di Cai; Yanliang Guo; et al. (Journal of Environmental Chemical Engineering, 2026)

MXene/LiFePO4 heterostructure for lithium recovery in flow-electrode capacitive deionization - Xinying Qiao; Ruiyang Ma; Haolin Li; Duo Yang; Xi Yu; Qian Yang; Zhichang Xiao; Xiaoxian Zhao; Shuaihua Zhang; Zhi Wang (Chemical Engineering Journal, 2026)

Effects of artificial reefs on the spatial and temporal distribution and ecological niche dynamics of rockfish (Sebastes spp.): an integrated analysis using environmental DNA and species distribution models - Yongjun Shang; Haolin Yu; Liyou Zhang; Tao Zhang; Yanli Tang (Fisheries Science, 2026)

An extracellular miRNA reshapes cell wall integrity to prime systemic immunity in tomato - Yue Qiao; Yu Xia; Jianfei Shi; Zihan Song; Liying Jin; Lijie Xuan; Haolin Yang; Xiang Yu; Ruoshi Wang; Haiyan Liu; Ali Zhang; Jinfeng Chen; et al. (Molecular Plant, 2026)

Embankment protection-inspired interfacial engineering for ultrahigh-efficiency, stable tandem quantum dot light-emitting devices - Kuibao Yu; Zhihan Lin; Tian Liu; Haolin Luo; Chao Zhong; Hao Liu; Fushan Li; Hailong Hu (Chemical Engineering Journal, 2026)

Service quality and behavioral acceptance under mandatory car restrictions: post-implementation evidence from Changdao Island, China - Hongwei Yu; Zijie Liu; Haolin Zhang; Youchao Xing; Yufeng Hou; Feng Liu (Transportation Research Part D: Transport and Environment, 2026)

Exploration of the preparation of N-doped biochar under the synergistic effect of urea and KOH from kinetic and thermodynamic perspectives - Linghui Yu; Shouzhi Li; Haolin He; Haoyu Yao; Wei Chen (Biomass and Bioenergy, 2026)

Black carbon in urban Jinan: Variations, health risks, and driving factors analyzed with machine learning - Jiaqi Chen; Wenbin Yu; Xiaohan Cui; Qingzhu Zhang; Tianshuai Li; Xinfeng Wang; Yuchao Ren; Haolin Wang; Qiao Wang (Journal of Environmental Sciences, 2026)

Evaluating bio-carbon sequestration in Beibu Gulf marine ranching areas via EwE modelling and LMDI analysis - Wei Guo; Jie Feng; Haiyan Wang; Zhen Zhang; Shuang Liang; Tao Zhang; Haolin Yu (Estuarine, Coastal and Shelf Science, 2026)

Ecological characteristics and carrying capacity analysis of marine ranching ecosystem in Beibu Gulf based on Ecopath model - Cheng Cheng; Haolin Yu; Jie Feng; Yan Li; Qingxian Cao; Li Liu; Cheng Yang; Shan Zhao; Shuo Li; Zhen Zhang; Haiyan Wang; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Upcycling polycrystalline silicon from waste solar cells for thermally conductive epoxy composites: Anisotropic crystallite growth and tailored microstructure via heat treatment - Yoon Hye Han; Kyung Hoon Min; Hye In Kang; Yu Min Lim; Haolin Wang; Hyunseong Shin; Sang Eun Shim (Chemical Engineering Journal, 2025)

Preparation high-efficiency NH2-MIL-125@g-C3N4 NADH photo-regeneration catalyst for enzymatic conversion of furfural to furfural alcohol - Shuaizhe Li; Xingyong Li; Senshen Yu; Qingtao Wang; Na Liu; Yichen Nie; Xuexiang Fu; Mengke Dong; Haolin Li; Yanliang Guo; Phidsavard Keomeesay; Shijie Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Hypoxia-responsive polyphenol prodrug for targeted glucose oxidase delivery and enhanced multimodal cancer therapy - Jiang Yu; Ruiping Huang; Jinbo Li; Zhaomeng Wang; Baoyue Zhang; Zhaochu Xu; Yuhang Wang; Jianying Ye; Tengfei Zhou; Haolin Zhang; Yubo Liu; Xin Li; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst” [Chem. Eng. J. 513 (2025) 162965] - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Molecular cloning, expression analysis, and functional characterization of Intelectin-1 from Chinese giant salamanders (Andrias davidianus) - Haolin Mo; Kexin Liu; Xiaoran An; Yongqing Chen; Jiajia Yu; Huixia Yu; Mingxing Yao; Weijia Song; Yang Li; Lixin Wang (Genes & Genomics, 2025)

Scalable solar-driven reforming of alcohol feedstock to H2 using Ni/Zn3In2S6 photocatalyst - Denny Gunawan; Tahlia Stern; Jiajun Zhang; Jodie A. Yuwono; Jian Pan; Qiyuan Li; Haolin Yu; Michael Gunawan; Rosalie K. Hocking; Cui Ying Toe; Jason Scott; Rose Amal (Chemical Engineering Journal, 2025)

Magnetic field oriented dual site S-Ni,FeOOH-M nanoarrays for enhanced oxygen evolution at high current densities - Jie Yu; Haolin Cheng; Yan Fu; Jinli Zhang (Chemical Engineering Journal, 2025)

Predicting Convectively Induced Turbulence With Regionally Convection-Permitting Simulations - Haoming Chen; Christy Yan-yu Leung; Ping Cheung; Haolin Liu; Sai Tick Chan; Xiaoming Shi (Asia-Pacific Journal of Atmospheric Sciences, 2025)
Convectively induced turbulence (CIT) is a severe aviation hazard. It is challenging to forecast CIT because low-resolution models cannot explicitly resolve convective motions at kilometer scales. In this study, we used the Model for Prediction Across Scales (MPAS) to simulate CIT cases with convection-permitting resolution ( $$\sim $$ ∼ 1 km) in the region of the CIT events and coarse resolution in other parts of the globe. We developed a method to estimate the eddy dissipation rate (EDR) using the resolved wind field of the MPAS simulations. The method is based on explicit filtering and reconstruction in the turbulence modeling for large-eddy simulations (LES). It estimates turbulence kinetic energy (TKE), which is then used to derive EDR. The new method produces different turbulence distribution and intensity than previous methods based on second-order structure functions and convective gravity wave drag, with higher accuracy and better correlation with observations for CIT cases tested in this study. The 1-km resolution simulation generates more accurate EDR and improves spatial patterns, but it is computationally demanding. The 3-km resolution can get benefits from reasonable accuracy and affordable computational cost. Because convection-permitting resolutions are in the gray zone for simulating convection, we evaluated the sensitivity of the prediction to the variations in physical and numerical schemes. Varying cumulus convection parameterization and monotonicity of numerical schemes are identified as practical approaches to generate beneficial ensemble spread. However, the physical perturbation-based ensemble has limitations, and initial condition perturbations are still necessary to encompass uncertainties in the development of convection.

Optimizing cropping systems and irrigation regimes to mitigate NH3 emissions and enhance crop productivity in the Huang-Huai-Hai Plain - Yanli Wang; Pengnian Wu; Haolin Yu; Jing Shao; Lingyun Li; Zhiheng Zhao; Peimeng Gao; Shilong Liu; Jinghui Wang; Xiaokang Guan; Pengfei Wen; Tongchao Wang (Field Crops Research, 2025)

Autocrine/paracrine fibroblast growth factor 1 (FGF1) enhances systemic lipid metabolism in rainbow trout fed with a high-fat diet by elevating uridine levels through the AMPK signaling pathway and activating the upp2 promoter via irf1 - Huixia Yu; Haolin Mo; Xiaoran An; Mingxing Yao; Jiuwei Gao; Jiajia Yu; Dongmei Xiong; Haixia Liu; Yang Li; Lixin Wang (Aquaculture, 2025)

Gaussian processes modeling for the prediction of polymeric nanoparticle formulation design to enhance encapsulation efficiency and therapeutic efficacy - Sihan Dong; Haolin Yu; Pascal Poupart; Emmanuel A. Ho (Drug Delivery and Translational Research, 2025)

A systematic study on the chemical model of polycyclic aromatic hydrocarbons formation from nutrients (glucose, amino acids, fatty acids) in food - Qiuyi Lin; Haolin Zhang; Xiaomei Lv; Ruiwei Xie; Bing-Huei Chen; Yu-Wen Lai; Lei Chen; Hui Teng; Hui Cao (Food Chemistry, 2024)

Exploring the roles of excess amino acids, creatine, creatinine, and glucose in the formation of heterocyclic aromatic amines by UPLC-MS/MS - Haolin Zhang; Xiaomei Lv; Weiming Su; Bing-Huei Chen; Yu-Wen Lai; Ruiwei Xie; Qiuyi Lin; Lei Chen; Hui Cao (Food Chemistry, 2024)

Influence of boundary layer jets on the vertical distribution of ozone in Guangdong, China - Yuanping He; Shaojia Fan; Yiming Wang; Yiming Liu; Xiao Lu; Haolin Wang; Cheng He; Chuying Mai; Yu Du (Science of The Total Environment, 2024)

“Transforming enemy into friend” strategy-based stimuli responsive dual-drug liposomes for synergistic chemo-photodynamic therapy - Jiang Yu; Baoyue Zhang; Jinbo Li; Zhaomeng Wang; Zhaochu Xu; Yuhang Wang; Tengfei Zhou; Ruiping Huang; Jianying Ye; Haolin Zhang; Chuang Zhang; Qingzhi Lv; et al. (Chemical Engineering Journal, 2024)

Geographical distribution and ecological niche dynamics of Crassostrea sikamea (Amemiya, 1928) in China's coastal regions under climate change - Bingxian Liu; Zhenqiang Liu; Cui Li; Haolin Yu; Haiyan Wang (Science of The Total Environment, 2024)

Enhancing productivity while reducing water footprint and groundwater depletion: Optimizing irrigation strategies in a wheat-soybean planting system - Pengnian Wu; Yanli Wang; Jing Shao; Haolin Yu; Zhiheng Zhao; Lingyun Li; Peimeng Gao; Yuming Li; Shuimiao Liu; Chenkai Gao; Xiaokang Guan; Pengfei Wen; et al. (Field Crops Research, 2024)

Evaluating optimized irrigation strategies on crop productivity and field water utilization under micro sprinkling irrigation in typical cropping systems of the Huang-Huai-Hai Plain - Pengnian Wu; Yanli Wang; Yuming Li; Haolin Yu; Jing Shao; Zhiheng Zhao; Yibo Qiao; Changshuo Liu; Shuimiao Liu; Chenkai Gao; Pengfei Wen; Xiaokang Guan; et al. (European Journal of Agronomy, 2024)

Identification and evolution characteristics of galectins and their roles in largemouth bass (Micropterus salmoides) following external stress - Jiajia Yu; Haolin Mo; Shuai Li; Debin Zhong; Mingmin Wang; Lu Tao; Zhihao Zhang; Lixin Wang (Aquaculture, 2024)

Autophagic and apoptotic proteins in goat corpus luteum and the effect of Adiponectin/AdipoRon on luteal cell autophagy and apoptosis - Haolin Li; Xiaomeng Pei; Hao Yu; Wei Wang; Dagan Mao (Theriogenology, 2024)

Optimized planting structures maintain system yield and economic benefits with less nitrogen footprint - Yanli Wang; Pengnian Wu; Yuming Li; Shuimiao Liu; Chenkai Gao; Yibo Qiao; Changshuo Liu; Jing Shao; Haolin Yu; Zhiheng Zhao; Xiaokang Guan; Pengfei Wen; et al. (Field Crops Research, 2024)

Optimizing irrigation strategies for sustainable crop productivity and reduced groundwater consumption in a winter wheat-maize rotation system - Pengnian Wu; Yanli Wang; Yuming Li; Haolin Yu; Jing Shao; Zhiheng Zhao; Yibo Qiao; Changshuo Liu; Shuimiao Liu; Chenkai Gao; Xiaokang Guan; Pengfei Wen; et al. (Journal of Environmental Management, 2023)

The potential for soil C sequestration and N fixation under different planting patterns depends on the carbon and nitrogen content and stability of soil aggregates - Yanli Wang; Pengnian Wu; Yibo Qiao; Yuming Li; Shuimiao Liu; Chenkai Gao; Changshuo Liu; Jing Shao; Haolin Yu; Zhiheng Zhao; Xiaokang Guan; Pengfei Wen; et al. (Science of The Total Environment, 2023)

Acute temperature stresses trigger liver transcriptome and microbial community remodeling in largemouth bass (Micropterus salmoides) - Jiajia Yu; Debin Zhong; Shuai Li; Zhihao Zhang; Haolin Mo; Lixin Wang (Aquaculture, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Dual role of NR4A1 in porcine ovarian granulosa cell differentiation and granulosa-lutein cell regression in vitro - Hao Yu; Jie Zhao; Xiaomeng Pei; Yuting Xia; Haolin Li; Wei Wang; Dagan Mao (Theriogenology, 2023)

Differences in selenium concentration and bioavailability between paddy and dryland soils of China: A study based on literature collection and field sampling - Yuanzhe Ma; Nanchun Zhang; Yanan Li; Haolin Zhao; Fei Zhou; Mingyue Xue; Lihui Lyu; Jing Yang; Yu Ban Man; Fuyong Wu; Dongli Liang (Journal of Hazardous Materials, 2023)

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species - Haolin Yu; Guangjie Fang; Kenneth A. Rose; Jiazheng Lin; Jie Feng; Haiyan Wang; Qingxian Cao; Yanli Tang; Tao Zhang (Frontiers in Marine Science, 2023)
Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explore 1) habitat usage and staying duration of individuals continuously exposed to 3, 5, and 7 mg/L dissolved oxygen (DO) in a complex of multiple preferred and avoided habitat types, and 2) the impact of ARs on exposure to different DO concentrations under a series of two-way replicated choice experiments with or without AR placement on the low-oxygen side. Six common reef-dependent species found in the northeastern sea areas of China were used (i.e., rockfish Sebastes schlegelii and Hexagrammos otakii , filefish Thamnaconus modestus , flatfish Pseudopleuronectes yokohamae , sea cucumber Stichopus japonicus , and crab Charybdis japonica ). Results showed that lower DO levels decreased the usage of preferred habitats of the sea cucumber and the habitat-generalist filefish but increased the habitat affinity to preferred habitat types for the two habitat-specific rockfishes. Low DO had no effect on the crab’s habitat usage. In the choice experiment, all three fish species avoided 1 mg/L, and the rockfish S. schlegelii continued to avoid the lower DO when given choices involving pairs of 3, 5, and 7 mg/L, while H. otakii and the flatfish showed less avoidance. The availability of ARs affected exposure to low DO for the habitat-preferring rockfishes but was not significant for the flatfish. This study provides information for assessing the ecological effects and potential for adaptation through behavioral movement for key reef-dependent species under the increasing overlap of ARs and hypoxia anticipated in the future.

Potential-dependent reconstruction of Ni-based cuboid arrays for highly efficient hydrogen evolution coupled with electro-oxidation of organic compound - Ruchun Li; Panyong Kuang; Swelm Wageh; Ahmed A. Al-Ghamdi; Haolin Tang; Jiaguo Yu (Chemical Engineering Journal, 2023)

Molecular cloning and functional characterization of melanocortin-3 receptor in grass carp (Ctenopharyngodon idella) - Haolin Mo; Huixia Yu; Yang Li; Timothy P. C. Ezeorba; Zhihao Zhang; Mingxin Yao; Jiajia Yu; Dongmei Xiong; Haixia Liu; Lixin Wang (Fish Physiology and Biochemistry, 2023)

Efficiency analysis and evaluation of centrifugal variable-rate fertilizer spreading based on real-time spectral information on rice - Yinyan Shi; Man Chen; Xiaochan Wang; Haolin Yang; Haiming Yu; Xiangze Hao (Computers and Electronics in Agriculture, 2023)

Comparison of 16S rRNA Gene Primers on Studying Microbial Community Composition in Bottom Water and Sediment of Artificial Reefs in Laoshan Bay, China - Guangjie Fang; Haolin Yu; Huaxiang Sheng; Yanli Tang; Zhenlin Liang (Journal of Ocean University of China, 2022)

Impact of summer moratorium on set-net fishery in Haizhou Bay, China - Guangjie Fang; Haolin Yu; Xinmeng Wang; Huaxiang Sheng; Yanli Tang; Changdong Liu; Chuanxi Chen; Zhenlin Liang (Journal of Oceanology and Limnology, 2022)

Relationships Between Community Structure and Environmental Factors in Xixiakou Artificial Reef Area - Haolin Yu; Wenzhao Yang; Changdong Liu; Yanli Tang; Xiefa Song; Guangjie Fang (Journal of Ocean University of China, 2020)